Modernisasi Persidangan Perkara Pidana Pasca Diterbitkannya Peraturan Mahkamah Agung Nomor 4 Tahun 2020 Tentang Administrasi Dan Persidangan Perkara Pidana Di Pengadilan Secara Elektronik - Kholilur Rahman (Universitas Islam Indonesia, 2021)
In the midst of a public health emergency, namely the Covid-19 Pandemic, it is not possible for the judiciary to conduct trials according to previously regulated standards. This is a big challenge for the Supreme Court to make all efforts to modernize the judiciary (judicial modernization) by deconstructing the judiciary and improving the quality of the judiciary for justice seekers. The formulation of the problem of this research, first, what is the ratio legis and the characteristics of electronic-based criminal trials (teleconference)? Second, the problem of implementing electronic criminal trials after the issuance of Perma Number 4 of 2020 concerning the Administration and Trial of Criminal Cases in Courts Electronically. The research method used is normative, using a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). The results of the study conclude, first, philosophically, namely preventing the spread of Covid-19 in the judiciary, based on the principle of